Bioinspired NADH Regeneration Based on Conjugated Photocatalytic Systems. Issue 2 (26th August 2020) - Zhang, Yuanyuan; Zhao, Yingjie; Li, Run; Liu, Jian
Abstract : Cofactors, such as nicotinamide adenine dinucleotide (NADH) or its phosphorylated derivative (NADPH), are playing essential roles in redox enzymatic catalysis because of their indispensable roles as biological hydride sources. However, due to its stoichiometric consumption, economic and efficient regeneration for NADH is of great importance for both in vivo and in vitro applications. Inspired by natural photosynthesis, photocatalytic NADH regeneration has drawn increasing attention, resulting from its mild reaction conditions and excellent biocompatibility with enzymes. Currently, various heterogeneous photocatalysts, such as conjugated small molecules, graphitic carbon nitride, carbon‐based materials, and organic polymers, are reported as promising candidates for photocatalytic NADH regeneration due to their outstanding advantages of low cost, high chemical stability, limited toxicity, and molecularly tunable optoelectronic properties. Herein, the key advances of conjugated photocatalytic systems for NADH regeneration are summarized, accompanied with their strengths and limitations. Finally, an outlook is tentatively attempted about the further developments of conjugated polymers–based NADH regeneration as well as integrated photoenzymatic catalysis. Abstract : Inspired by nature photosynthesis, conjugated photocatalytic systems, including conjugated molecular photosensitizers, carbon nitride photocatalysts, carbon‐based materials, and conjugated organic polymers, are widely applied to regenerate nicotinamide adenine dinucleotide (NADH), which can further couple with enzymatic synthesis for high‐value‐added chemicals in a sustainable manner.